Training experts in family medicine teaching. (2nd January 2016) - Švab, Igor; Allen, Justin; Žebiene, Egle; Petek Šter, Marija; Windak, Adam
ABSTRACT: Family medicine teachers require specific educational skills. A framework for their professional development is essential for future development of the discipline in Europe. EURACT developed a framework on educational expertise, and subsequently applied it in a curriculum of teaching-skills courses of various levels. The aim of this article is to describe the development of the teaching framework, and of an international three-level course programme for 'teaching-the-teachers'. Furthermore, we describe our experiences and lessons learned, in particular with regard to the level-three programme for proficient teachers, which was new. We conclude that it is possible to develop a theoretical framework of family medicine teaching expertise and to apply it in an international high-level educational programme for future experts in family medicine education. Research evidence of the usefulness of this approach is needed, and the threats for its further development into a sustainable activity are its high teacher/student ratio associated with relatively high costs and difficulties in recruiting suitable participants.